The blues of Flats Brown [compact disc, unabridged] - Myers, Walter Dean, 1937-2014 (Live Oak Media, 2002)
To escape an abusive master, a junkyard dog named Flats runs away and makes a name for himself from Mississippi to New York City playing blues on his guitar.